Self-defense mechanism of the main characters in the novel Pünktchen und Anton: A study of Sigmund Freud's psychoanalytic theory - Zahrah, Nada Muthia; Melky Ayu Wijayanti; Zuriyati; Siti Gomo Attas (Lililacs Journal, 2023)
Self-defense mechanism is part of Sigmund Freud's psychoanalytic theory. According to Freud, self-defense mechanism is an individual way of coping with anxiety-related outbursts. Anxiety can arise when there is a conflict of desire between the id and ego because the id gets a sex drive and aggression that forces the ego to do something it wants. The problem of individuals who overcome anxiety by self-defense can also occur in human "creation" in the form of characters in literary works, as in the novel. The novel to be studied in this research is a children's novel from Germany entitled Pünktchen und Anton by Erich Kästner. The main characters, Pünktchen and Anton, are still in elementary school. Pünktchen and Anton have different life problems from each other. This study aims to know in depth or to explore the type of self-defense mechanism used by the two main figures in the face of anxiety. This research is qualitative research with a content analysis method. The results show there are 31 data on self-defense mechanisms in this novel. Pünktchen uses the form of Repression 3 data, Reaction Formation 6 data, Displacement 1 data, Fixation 1 data, Disclaimer 1 data, and Rationalization 1 data. Anton uses the form of Repression 4 data, Reaction Formation 6 data, Displacement 3 data, Sublimation 2 data, and Rationalization 3 data. The second sub-focus on the type of personality of the main character, the results show Pünktchen used 4 data for id, 4 data for superego, and 1 data for ego. It means Pünktchen's personality is dominated by id and superego. Anton used 3 data for the id, 6 data for the ego, and 5 data for the superego. It means Anton has a healthy personality because he was dominated by his ego.